Konstytucja Apostolska "Ex corde Ecclesiae" – aktualna propozycja dla świata akademickiego - Michalski, Michał (Annales. Etyka w Życiu Gospodarczym, 2009)
Pope John Paul II’s Apostolic Constitution Ex Corde Ecclesiae is not a new document. It was published almost twenty years ago – in 1990. Nevertheless it seems that it’s not very well known in Poland. Although it is mainly addressed to Catholic universities, one has to admit that it gives insightful description of academic world’s nature in general. This constitution recalls basic objectives and calling of academia. Ex Corde Ecclesiae is an important voice that speaks about the mission and identity of university, which can be understood in two perspectives. First – in European dimension – it reminds us where Old Continent’s intellectual heritage and achievements come from. Secondly – in our Polish perspective – Apostolic Constitution Ex Corde Ecclesiae – may be a valuable signpost for our developing and reforming academic world, which not always seems to understand its identity and mission properly.